The role of laryngectomy in locally advanced thyroid carcinoma. Review of 16 cases (2018)
ABSTRACT: Locally advanced disease with larynx invasion is a challenge to the surgeon, but laryngectomy is almost never necessary in thyroid carcinoma. The aim of this study was to review the clinical outcomes of patients with locally advanced thyroid carcinoma invading the larynx who underwent laryngectomy. A case series of patients treated in a tertiary care hospital was reviewed. Data about the type of operation, method of reconstruction, complications and overall survival of 16 patients operated on between 2002 and 2015 with larynx invasion is presented. There were 10 females. The mean age was 63 ± 8.8 years. Besides total thyroidectomy and neck dissection, four patients underwent total pharyngolaryngectomy, 11 total laryngectomy and one hemi-laryngectomy. Reconstruction was made with regional flaps in 10 patients (7 pectoral/Bakamjian flaps and 3 gastric pull-through procedures) and a jejunum free flap in one patient. Two patients needed carotid artery reconstruction. Five tumours were classic (conventional) papillary carcinoma variants, while the others were aggressive histological varieties (insular, tall cell, sclerosing). The mean tumour size was 4.3 ± 1.6 cm. All tumours had lymphovascular invasion and 12 had positive lymph nodes. Concomitantly, oesophageal/hypopharyngeal invasion was present in 7 cases and invasion of carotid vessels in 2 cases. There were two postoperative deaths and two anastomotic leaks that were treated conservatively. The mean overall survival was 31 ± 33 months (median 27.6 months, range 0-120). Laryngectomy is an alternative surgical procedure to control selected cases of advanced thyroid carcinoma that offers good local control and long term survival. RIASSUNTO: Le malattie localmente avanzate con invasione della laringe sono una sfida per il chirurgo, tuttavia la laringectomia non si rende quasi mai necessaria nel carcinoma della tiroide. L’obiettivo di questo studio è stato quello di valutare gli outcomes clinici di quei pazienti sottoposti a laringectomia per carcinoma della tiroide localmente avanzato con invasione della laringe. Sono stati inclusi una serie di pazienti trattati in presidi ospedalieri di terzo livello. Pertanto sono stati raccolti i dati riguardo il tipo di intervento, la modalità di ricostruzione, le complicanze e la sopravvivenza di sedici pazienti operati tra il 2002 e il 2015. Tra questi, 10 erano donne; l’età media era di 63 ± 8,8 anni. Oltre alla tiroidectomia totale e alla dissezione del collo, quattro pazienti sono stati sottoposti a faringolaringectomia, undici a laringectomia, e uno ad emilaringectomia. La ricostruzione è stata effettuata con lembi regionali in dieci pazienti (7 lembi di pettorale e 3 procedure di pull-though gastrico) e lembo libero di digiuno in un paziente. Per due pazienti si è resa necessaria la ricostruzione dell’arteria carotide. Cinque tumori erano carcinomi papillari variante classica, gli altri erano varianti istologiche aggressive (insulare, sclerosante diffuso, a cellule alte). La dimensione media dei tumori era 4,3 ± 1,6 cm. Tutti i tumori presentavano un’invasione linfovascolare e dodici di essi avevano dato metastasi linfonodali. Sette casi presentavano una concomitante invasione ipofaringo-esofagea, mentre due casi presentavano invasione dei vasi carotidei. Ci sono state due morti postoperatorie e due deiscenze dell’anastomosi, trattate entrambe in maniera conservativa. La sopravvivenza media è stata di 31 ± 33 mesi (media pari a 27,6, range 0-120). La laringectomia è una procedura chirurgica per casi selezionati di carcinoma tiroideo, che offre un buon controllo locale e lunghi tempi di sopravvivenza.